1995
DOI: 10.1007/bf00187164
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of classical intrafascial-supracervical hysterectomy (CISH) with transuterine mucosal resection as performed by pelviscopy and laparotomy—our first 200 cases

Abstract: A novel way of performing endoscopic intrafascial supracervical hysterectomy is presented. By using the endoscopic approach for dissection as well as uterine extraction using the serrated-edged macro-morcellator, we avoid giving the patient a colpotomy incision and its inherent post-operative discomfort. A further modification involves nearly complete excision (95%) of uterocervical mucosa using a calibrated resection tool, thus eliminating the possible subsequent development of cervical stump neoplasia. Spari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Figure 7 showed that the uterine weights less than 200 g were removed by IVH and pelviscopic CISH operations, while larger size uteri weighing less than 400 g in average were treated by AH and laparotomy CISH operations. Operating time (1993)(1994) FIGURE 6 Operating time of 368 hysterectomies of patients who underwent hysterectomy at the Department of Obstetrics and Gynaecology University of Kiel (1993)(1994) (1993)(1994) LpCISII FIGURE 7 Uterine weights of 368 hysterectomies of patients who underwent hysterectomy at the Department of Obstetrics and Gynaecology University of Kiel (1993Kiel ( -1994 The shortest period of postoperative hospitalization was found among the patients, undergoing pelviscopic CISH operations (Fig. 8) [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 showed that the uterine weights less than 200 g were removed by IVH and pelviscopic CISH operations, while larger size uteri weighing less than 400 g in average were treated by AH and laparotomy CISH operations. Operating time (1993)(1994) FIGURE 6 Operating time of 368 hysterectomies of patients who underwent hysterectomy at the Department of Obstetrics and Gynaecology University of Kiel (1993)(1994) (1993)(1994) LpCISII FIGURE 7 Uterine weights of 368 hysterectomies of patients who underwent hysterectomy at the Department of Obstetrics and Gynaecology University of Kiel (1993Kiel ( -1994 The shortest period of postoperative hospitalization was found among the patients, undergoing pelviscopic CISH operations (Fig. 8) [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…From 1950 onwards hysterectomy was almost only performed as total hysterectomy. Since the 1990 interest in supracervical hysterectomy has been re-established because of the introduction of the Classic Intrafascial Supracervical Hysterectomy pelviscopic and laparotomy techniques [3][4][5][6][7][8][9]. Previously, in 1984 (1993)(1994) (per cent), (n=368, 1993-1994) …”
Section: Introductionmentioning
confidence: 99%
“…These techniques have primarily been applied to laparoscopic removal of intra-abdominal organs or vaginal hysterectomy [10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. A number of instruments and techniques have been described utilising instruments with mechanically operated blades or high-frequency cutting electrodes, however surgical instruments such as ring forceps and digital manipulation have also been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…14 Different variants evolved, such as laparoscopy-assisted vaginal hysterectomy (LAVH) and LASH, as well as TLH and laparoscopic intrafascial hysterectomy. TLH had a steep learning curve and, in the beginning, a relatively high complication rate.…”
Section: Development Of Laparoscopic Hysterectomy Techniques and Instmentioning
confidence: 99%